#1

Could you show me the steps in proving this?

tan(θcot(θ-cos^2(θEquals sin^2(θ

tan(θcot(θ-cos^2(θEquals sin^2(θ

#2

tan(θ = sin(θ / cos(θ

cot(θ = cos(θ / sin(θ

So...

(sin(θ/cos(θ) * (cos(θ/sin(θ) - cos^2(θ = sin^2(θ

The tan * cot simplifies to 1, so you have 1 - cos^2(θ = sin^2(θ, which is true.

Next time, Math help thread.

cot(θ = cos(θ / sin(θ

So...

(sin(θ/cos(θ) * (cos(θ/sin(θ) - cos^2(θ = sin^2(θ

The tan * cot simplifies to 1, so you have 1 - cos^2(θ = sin^2(θ, which is true.

Next time, Math help thread.

#3

This confirms my theory of darkstar being an evil genius bent on global destruction.

#4

tan(θ = sin(θ / cos(θ

cot(θ = cos(θ / sin(θ

So...

(sin(θ/cos(θ) * (cos(θ/sin(θ) - cos^2(θ = sin^2(θ

The tan * cot simplifies to 1, so you have 1 - cos^2(θ = sin^2(θ, which is true.

Next time, Math help thread.

Thanks a ton man, I'll go there in te future!

#5

Do your own homework...

#6

This confirms my theory of darkstar being an evil genius bent on global destruction.

#7

wat

Jesus, as much as I'd love to be a sound engineer, math scares the hell out of me

Jesus, as much as I'd love to be a sound engineer, math scares the hell out of me

#8

Could you show me the steps in proving this?

tan(θcot(θ-cos^2(θEquals sin^2(θ

tan(42)cot(42)-cos^42(42) = sin^42(42)

What's there to proove?

#9

tan(42)cot(42)-cos^42(42) = sin^42(42)

What's there to proove?

#10

(Invalid img)

Doesnotgetreference,brainexploded.

#11

Doesnotgetreference,brainexploded.

Do you even get your own reference?

#12

Do you even get your own reference?

Yes, yes i do.

EDIT: I just got the towel

*Last edited by Deadlock Riff at Nov 6, 2011,*